Development and antioxidation of metal ion chelating packaging film. (June 2022) - Yu, Zhen; Lu, Lixin; Lu, Lijing; Pan, Liao; Qiu, Xiaolin; Tang, Yali
Abstract: Lipid oxidation is one of the important causes for the degradation of food quality, and trace transition metal ions in food can catalyze lipid oxidation. To inhibit the catalytic action of the metal ions, chitosan (CS) and sodium alginate (SA) multilayers were assembled on the polypropylene (PP) surface grafted with polyacrylic acid (PAA) to obtain PP-g-PAA/(CS/SA)10.5 antioxidant active packaging film. The relationship between the parameters of polyelectrolyte solution were analyzed, and the results reflected that the SA and CS had both characteristics of electrolytes and polymers. The influence of polyelectrolyte solution parameters on chemical structure and physical morphology of the active film was studied, and Cu(II) chelating ability of the sample 1.0–5.0 and 5.0–5.0 improved about 8.57% and 18.75% respectively compared with PP-g-PAA film. In addition, the oil-in-water emulsion was used as food simulation, the results showed that the conjugated diene value of PP was 2.0 times higher than that of the sample 1.0–5.0 on the 19th day; on the 56th day, the n-hexanal content of PP reached 24.09 mg/L, while the sample 1.0–5.0 maintained at 0.28–0.61 mg/L. All the results proved that the PP-g-PAA/(CS/SA)10.5 film had good antioxidant protection. Highlights: A non-releasing antioxidant active packaging film PP-g-PAA/(CS/SA)10.5 was prepared. The film inhibited oxidation by chelating trace transition metal ions in food. The bio-polymer and petroleum-polymer were as inner and outer layers of the film. The optimal polyelectrolyte solution was 1.0 mg/mL concentration and 5.0 pH. The antioxidation of 0.6 cm 2 /mL film was close to 0.01 mol/L EDTA in food simulator.